Procesos En La Gestión Financiera Del Gad Del Cantón Baba - Sánchez Morán, Jessenia Carolina (2017)
Through its new administration, the Bona Municipal Decentralized Autonomous Government is undergoing a process of improvement in financial management, in order to comply with the programs, projects and works that will be used for the development of the entire Baba canton. A Financial Management model allows an institution such as the Baba Municipal Decentralized Autonomous Government to develop its activities under a system of interrelated processes, in order for the entity to maintain an efficient and effective financial support, to keep strictly controlled financial resources so that they are used in a transparent, correct and timely manner. The research work is developed within the line of research Accounting Information Management, which will be developed under a field research and interviews with the officials of the financial department to know the procedures that are used for the development of the activities, supported by a documentary base because it will have to analyze the laws, codes related to the competences and attributions of the Municipal GAD such as COOTAD.